Las referencias corporales en el De Regno de Tomás de Aquino (Argos, 2025)
The aim of this article is to analyze the senses that receive in context the corporal references in Thomas Aquinas' De Regno. A rich use of the images and remissions to the human body is evident, as much for its symbolic connotations as for the functions that they fulfill in the general argumentation of a pioneering text in the history of the medieval political thought.
Keywords: Thomas Aquinas; politic; metaphor; body